El rol de la familia en el proceso de aprendizaje en tiempos de confinamiento en estudiantes de educación inicial de la escuela de educación básica Huayna Capac del cantón Caluma, año lectivo 2020 - 2021 - Lombeida Galeas, Darwin Geovanny (2021)
The present Educational Intervention project called The Role of the family in the learning process in times of confinement in initial education students of the Huayna Capac Basic Education School of the Caluma Canton, school year 2020 - 2021, has the purpose of determining the role that the family plays and fulfills in the educational process of students as a result of the pandemic caused by COVID-19 and the subsequent confinement in homes, as this has triggered multiple and varied limitations in terms of access to inclusive education and Integral that as of March of this year became exclusively virtual. The research allowed to highlight the importance that parents and representatives of the students of the Educational Unit have during the teaching-learning process of their children, because due to the suspension of face-to-face academic activities due to the health emergency; This work became very relevant for the educational community of the institution due to all the pedagogical and strategic implications involved in designing strategies that allow the development of adequate and effective accompaniment. The work was descriptive because it allowed us to analyze the object of study in the context in which it is developed without manipulation of any kind on the part of the researchers, being able to be analyzed in the real context of the pandemic in a general way, complemented with the particular analysis carried out to the identified application dimensions, supported by teaching experiences that are developed day by day in the educational institution. The limited participation of the family in academic activities within the home was evidenced, as well as low correspondence between the institution and parents, since there are family realities such as the level of preparation, available resources, so many materials. Pre-intervention surveys were applied to define the situational state of the family within the homes and the conditions in which children develop their academic activities 14 around school accompaniment; Once the intervention was carried out, the effectiveness of the workshops given to relatives was determined, finding a high rate of effectiveness in terms of increasing family participation within school activities. Keywords: